Effect of ampicillin, streptomycin, penicillin and tetracycline on metal resistant and non-resistant Staphylococcus aureus - Chudobova, Dagmar; Dostalova, Simona; Blazkova, Iva; Michalek, Petr; Ruttkay-Nedecky, Branislav; Sklenar, Matej; Nejdl, Lukas; Kudr, Jiri; Gumulec, Jaromir; Tmejova, Katerina; Konecna, Marie; Vaculovicova, Marketa; et al. (International journal of environmental research and public health, 2014)
There is an arising and concerning issue in the field of bacterial resistance, which is confirmed by the number of deaths associated with drug-resistant bacterial infections. The aim of this study was to compare the effects of antibiotics on Staphylococcus aureus non-resistant strain and strains resistant to cadmium or lead ions. Metal resistant strains were created by the gradual addition of 2 mM solution of metal ions (cadmium or lead) to the S. aureus culture. An increasing antimicrobial effect of ampicillin, streptomycin, penicillin and tetracycline (0, 10, 25, 50, 75, 150, 225 and 300 µM) on the resistant strains was observed using a method of growth curves. A significant growth inhibition (compared to control) of cadmium resistant cells was observed in the presence of all the four different antibiotics. On the other hand, the addition of streptomycin and ampicillin did not inhibit the growth of lead resistant strain. Other antibiotics were still toxic to the bacterial cells. Significant differences in the morphology of cell walls were indicated by changes in the cell shape. Our data show that the presence of metal ions in the urban environment may contribute to the development of bacterial strain resistance to other substances including antibiotics, which would have an impact on public health.
Keywords: Microbial Sensitivity Tests; Drug Resistance, Bacterial; kadmium; Staphylococcus aureus; Cadmium; bakteriální léková rezistence; mikrobiální testy citlivosti; Anti-Bacterial Agents; Lead; antibakteriální látky; olovo